The influence of swimming start components for selected Olympic and Paralympic swimmers - Burkett, B.; Mellifont, R.; Mason, B. (Journal of Applied Biomechanics, 2010)
This study compared the components of the 15-m swimming start for 20 international male Olympic and Paralympic swimmers. The time, distance, and velocity components for freestyle swimming were measured. There were significantly (p < .05)different absolute and relative swim start measures among the swimming groups. Using stepwise regression three variables significantly influenced the start to 15-m time: (i) underwater velocity, (ii) free swim velocity, and (iii) whether the swimmer had cerebral palsy. This new knowledge provides useful information for swimmers and coaches on which components to prioritize, along with the practical applications of improving the streamline position to increase underwater velocity and to ensure that the transition from underwater to surface breakout occurs at the optimal time for maximum free swim velocity.